Justice capital: A model for reconciling structural and agentic determinants of desistance - Best, David Wilhelm (Probation journal, 2021)
The emerging literature on desistance (and recovery from addictions) has focused on key life-course transitions that can be characterised as the need for jobs (meaningful activities), friends (transitioning to pro-social) and houses (a home free from threat). The term ‘recovery capital’ is used to characterise personal, social and community resources an individual can draw upon to support their recovery, partly bridging agentic (personal) and structural (community) factors. The development of the concept of ‘justice capital’ furthers this reconciliation, by focusing on resources an individual can access and the resources that an institution can provide. We build on this by outlining the concept of institutional justice capital (IJC) to examine the role of criminal justice institutions in supporting or suppressing justice capital, particularly for marginalised groups. We use a case study approach, drawing on recent studies in prisons in Australia and the United Kingdom to develop a model of justice capital at an institutional level and discuss how this can shape reform of prisons and can be matched to the needs of offenders. The paper concludes with a discussion of future directions in implementing an IJC model, to deliver a strengths-based approach to promoting desistance and creating a metric for assessing the rehabilitative activities of institutions.